Exploration on the Action-Oriented Teaching Mode of Higher Vocational Political Courses under the Background of Internet + Education - Jiafang Li (Advances in Multimedia)
With the advancement of the “Internet +” time, school lessons, family education, and social education, today’s college students present some characteristics that are different from those of previous college students. They are more active, dare to express, have the courage to express, can acquire knowledge through various channels such as the Internet, and are extremely concerned about current hot topics or current affairs. Therefore, they have higher requirements for teaching content and are not interested in outdated knowledge topics. Therefore, looking at mobile phones in class is a common phenomenon in college classrooms, which brings great confusion to teachers’ teaching. The so-called water can carry a boat and it can also capsize it. When the flood comes, it cannot be blocked, so we need to find a way to divert it. In this paper, by adopting the personalized recommendation algorithm based on collaborative filtering, the recommendation algorithm in the recommendation system is applied to the action-oriented online teaching platform of higher vocational political courses, and a hybrid programming method of cross-platform compatibility HTML5 and high-performance MUI framework is designed. Personalized online education platform for political courses in higher vocational colleges is based on a collaborative filtering algorithm. The server-side development selects a mature B/S architecture, adopts the currently popular MVC5 development model, and uses HTML5 and MUI frameworks for mobile terminals. In order to improve the effectiveness of ideological and political courses in higher vocational colleges, a three-in-one ideological and political course teaching model with thematic action orientation, “Internet +” action orientation, and practical action orientation has been explored, and good educational and teaching effects have been achieved.